Energy poverty and obesity - Prakash, Kushneel; Munyanyi, Musharavati Ephraim (My University, 2021)
Obesity is a major health concern in both developed and developing nations. Yet, evidence on the determinants of obesity is relatively limited. We contribute to the literature on the determinants of obesity by empirically examining the effects of energy poverty on obesity. Using 14 waves of the Household, Income and Labour Dynamics in Australia (HILDA) survey, we find energy poverty is positively associated with obesity. Applying linear probability model, our estimates suggest that being energy poor results between 1.4 and 2.5 percentage points increase in the probability of being obese, depending on how energy poverty is measured. Our results are robust to alternative modelling techniques, inclusion of additional control variables and potential influence of unobservable. We also find that amount of sleep, health status and level of psychological distress are important transmission channels through which energy poverty influences the probability of being obese.
Energy Economics
Keywords: Health and wellbeing; Housing, communities and neighbourhoods